Identification of growth-dependent transcripts in the haloalkaliphilic archaeon Natrialba magadii - Madrid, Enrique A. (2012)
The transition from balanced growth to the stationary phase induces changes in the morphology and physiology of most bacteria with the aim of preparing the cells to withstand unfavorable conditions (Nystrom, 2004; Siegele and Kolter, 1992). In Archaea, the third domain of life, many species are extremophiles, meaning that they have adapted their physiology to optimally live in environments with conditions that are lethal for most life forms. The effect of the growth stage in archaeal physiology has been investigated to a limited extent (Lange et al., 2007) and may reveal conserved as well as novel strategies of adaptation. The accurate regulation of gene expression is essential in all living cells for the adaptation to different environmental conditions (Soppa, 2006). In the haloarchaea (optimum growth at ＞2 M NaCl) growth phase-dependent gene expression has been investigated through genomewide analysis of transcription and/or translation in the neutrophilic species Haloferax volcanii and Halobacterium salinarum (Facciotti et al., 2010; Lange et al., 2007). These studies showed that a signifi cant fraction of genes were subjected to differential transcriptional and/or translational control; however, neither the fractions nor the identity of the regulated genes were conserved between these archaea.